2014
DOI: 10.1590/s0102-86502014000500002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human chorionic gonadotropin on the normal testicular tissue of rats

Abstract: PURPOSE:To investigate the effects of human chorionic gonadotropin (hCG) on the testicular tissue of young male rats. METHODS:Male Wistar rats were assigned to groups (10 rats/group).Control Group received subcutaneous saline solution; Group 1 received hCG 50UI/Kg/dose; and Group 2 received hCG 100UI/Kg/dose, daily for 15 days. Half was submitted to bilateral orchiectomy on the 16 th day and the other half 45 days after the beginning of the hormone application. Testicles were weighed, measured and has their vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…At least eight sections from each testis per animal were evaluated for histopathological changes using a Nikon Eclipse 80‐i microscope. About 25 seminiferous tubules from left as well as right testis per animal were selected randomly for measurement of their diameter and circumference using Motic Images Plus 3.0 ML software, as described previously (Montoto et al, ; Altoè et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…At least eight sections from each testis per animal were evaluated for histopathological changes using a Nikon Eclipse 80‐i microscope. About 25 seminiferous tubules from left as well as right testis per animal were selected randomly for measurement of their diameter and circumference using Motic Images Plus 3.0 ML software, as described previously (Montoto et al, ; Altoè et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Motic Image Plus 2.0 Ml was used for the analysis of images (Altoé et al, 2014). Totally, 10 sections of seminiferous per animal were measured.…”
Section: Morphometric Assessment Of Seminiferous Tubulesmentioning
confidence: 99%
“…Such sensitivity influences the process of spermatogenesis, leading to the impairment in fertility. The evaluation of the properties of seminiferous tubules, that is, morphological and morphometric parameters is a simple method for the assessment of the changes in the spermatogenesis process (Altoé et al, ; Soltani et al, ). The spermatogenic process could be decreased by detrimental alterations in the function of stem cells, resulting in degeneration of spermatogonial cells and phagocytosis by Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
“…The spermatogenic process could be decreased by detrimental alterations in the function of stem cells, resulting in degeneration of spermatogonial cells and phagocytosis by Sertoli cells. Also, the exposure of spermatogonial cells to environmental toxicity can also make a delay on the process of spermatogenesis and even cause apoptosis and degeneration in germ cells, eventually resulted in hormonal dysfunction and infertility problem (Altoé et al, ). Numerous research has shown that the spermatogenesis process is influenced by gonadotropins and androgens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation